Targeting the blood-brain barrier to delay aging-accompanied neurological diseases by modulating gut microbiota, circadian rhythms, and their interplays - Yanping Wang; Weihong Du; Xiaoyan Hu; Xin Yu; Chun Guo; Xinchun Jin; Wei Wang (Elsevier, 2023)
The blood-brain barrier (BBB) impairment plays a crucial role in the pathological processes of aging-accompanied neurological diseases (AAND). Meanwhile, circadian rhythms disruption and gut microbiota dysbiosis are associated with increased morbidity of neurological diseases in the accelerated aging population. Importantly, circadian rhythms disruption and gut microbiota dysbiosis are also known to induce the generation of toxic metabolites and pro-inflammatory cytokines, resulting in disruption of BBB integrity. Collectively, this provides a new perspective for exploring the relationship among circadian rhythms, gut microbes, and the BBB in aging-accompanied neurological diseases. In this review, we focus on recent advances in the interplay between circadian rhythm disturbances and gut microbiota dysbiosis, and their potential roles in the BBB disruption that occurs in AAND. Based on existing literature, we discuss and propose potential mechanisms underlying BBB damage induced by dysregulated circadian rhythms and gut microbiota, which would serve as the basis for developing potential interventions to protect the BBB in the aging population through targeting the BBB by exploiting its links with gut microbiota and circadian rhythms for treating AAND.